O impacto da vagotomia associada ou não a esplenectomia sobre o tecido adiposo branco de ratos obesos e não obesos - Kuchler, Joice Cristina (2021)
The vagus nerve and the spleen represent a complex interface between neural and immunological functions with repercussions on energy metabolism and on the content of white adipose tissue (WAT). In this work, we evaluated the effect of vagotomy associated with splenectomy on the content of WAT, histology and expression of interleukin 10 (IL-10) in male Wistar rats with hypothalamic obesity or not. Hypothalamic obesity was induced by neonatal administration of monosodium glutamate (M; 4g / Kg). Non-obese or control rats (CTL) received equimolar saline. At 60 days of age, M-obese and CTL rats were randomly assigned to experimental subgroups according to the surgical procedure: simulation; subdiaphragmatic vagotomy (SV); splenectomy (SPL) and SV + SPL (n = 11 rats / group). At 150 days of life and after 12 hours of fasting, the rats were sacrificed, blood was collected, visceral and subcutaneous deposits were excised, weighed and related to the histological process, with analysis of the number and size of adipocytes and protein expression of IL-10. M-obese rats aggregated greater adiposity, plasma levels of IL-10, hyperinsulinemia, hypertriglyceridemia and insulin resistance in relation to the CTL groups (p <0.05). In CTL and M-obese rats, SV reduced body weight gain and triglyceride levels by decreasing the size of adipocytes without altering IL-10 expression in TAB (p <0.05). The absence of the anterior spleen the effects of VS on adiposity and metabolism in CTL animals, but not in M-obese rats. SV increased plasma levels of IL10 in the CTL group, a response avoided by the absence of the spleen. Neither VS and/or ESP surgeries modify the plasma levels of IL-10 in M-obese rats. In conclusion, vagotomy promotes a reduction in body weight and adiposity, increasing plasma levels of IL-10 in non-obese animals, actions that depend on the presence of the spleen. Under conditions of obesity, vagotomy also reduces body weight, adiposity and improves insulin sensitivity without altering plasma levels of IL-10. However, it was observed that in conditions of obesity, the spleen does not participate in the effects of vagotomy. Thus, we have shown in an unprecedented way that metabolism and fat mass are regulated by several mechanisms of interaction between vagal and splenic activity in conditions of health and obesity.